2017
DOI: 10.1093/mnrasl/slx169
|View full text |Cite
|
Sign up to set email alerts
|

Connecting traces of galaxy evolution: the missing core mass–morphological fine structure relation

Abstract: Deep exposure imaging of early-type galaxies (ETGs) are revealing the second-order complexity of these objects, which have been long considered uniform, dispersionsupported spheroidals. "Fine structure" features (e.g. ripples, plumes, tidal tails, rings) as well as depleted stellar cores (i.e. central light deficits) characterize a number of massive ETG galaxies, and can be interpreted as the result of galaxy-galaxy interactions. We discuss how the timescale for the evolution of cores and fine structures are c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
1
2
0
Order By: Relevance
“…When the merger relic hosts a BHB, the density profile is noticeably carved out beyond the radius including two times the BHB mass; this is a well established result (e.g. Milosavljević & Merritt 2001;Gualandris & Merritt 2012) and is supported by observations (Ferrarese et al 1994;Lauer et al 1995;Bonfini et al 2018). As a matter of fact, even the infall of a single MBH can produce a core in the system (Gualandris & Merritt 2008;Goerdt et al 2010); however our simulations suggest that in the single MBH scenario the effect of core scouring is significantly smaller compared to the BHB case (Figure 13, central panel).…”
Section: One or Two Mbhssupporting
confidence: 57%
“…When the merger relic hosts a BHB, the density profile is noticeably carved out beyond the radius including two times the BHB mass; this is a well established result (e.g. Milosavljević & Merritt 2001;Gualandris & Merritt 2012) and is supported by observations (Ferrarese et al 1994;Lauer et al 1995;Bonfini et al 2018). As a matter of fact, even the infall of a single MBH can produce a core in the system (Gualandris & Merritt 2008;Goerdt et al 2010); however our simulations suggest that in the single MBH scenario the effect of core scouring is significantly smaller compared to the BHB case (Figure 13, central panel).…”
Section: One or Two Mbhssupporting
confidence: 57%
“…Prugniel et al (1988) also point out that this galaxy might be in an advanced merger state which would significantly affect our dynamical models. Large scale signatures of this merger (such as shells) are also visible in the MATLAS images from Duc et al (2015), also shown in Bonfini et al (2018). However, Krajnović et al (2011) analyzed the ATLAS 3D kinematics of NGC 3640 with Kinemetry (Krajnović et al 2006) and found only very small residuals and a very regular shape within one R e , indicating that the center of NGC 3640 is relaxed now.…”
Section: Kinematic Resultsmentioning
confidence: 72%
“…This mechanism possibly justifies the almost ubiquitous presence of stellar cores at the centre of the most massive galaxies (i.e. the ones that likely experienced the largest number of mergers; Bonfini et al 2018).…”
Section: Hardening In Stellar Environmentsmentioning
confidence: 92%